Synergism of Al-containing solid electrolyte interphase layer and Al-based colloidal particles for stable lithium anode. (June 2017) - Ye, Huan; Yin, Ya-Xia; Zhang, Shuai-Feng; Shi, Yang; Liu, Lin; Zeng, Xian-Xiang; Wen, Rui; Guo, Yu-Guo; Wan, Li-Jun
Abstract: Trace water in nonaqueous electrolytes has been supposed to be detrimental to Li metal, which may induce formation of HF and corrode battery materials. Herein, we propose that a controllable AlCl3 is an efficient electrolyte additive for dendrite-free Li deposition. The additive could react with trace water in the electrolyte to form a stable Al2 O3 -rich solid electrolyte interphase (SEI) layer on the surface of Li and Al-based positively charged colloidal particles (PCCPs) in the electrolyte. PCCPs could form a positively charged electrostatic shield around the protruding lithium during the deposition process and induce the subsequent deposition of Li to the adjacent regions of the protruding Li, enabling a uniform and dendrite-free Li morphology. The assembled Li|Se and Li|Li4 Ti5 O12 batteries benefit from the synergism of SEI layer and PCCPs, thereby demonstrating the impressive capability for dendrite suppression of Li anode and improved electrochemical performance. Graphical abstract: Highlights: Dendrite-free Li morphology can be achieved with controllable AlCl3 as efficient electrolyte additive. AlCl3 reacts with trace water to form a stable Al2 O3 -rich SEI layer and Al-based colloidal particles. Synergism of SEI and colloidal particles enables well suppression of Li dendrites and improved electrochemical performances.